Нариси історії розвитку прикладних технічних наук в Україні. З досвіду Харківського політехнічного інституту - Тверитникова, Олена Євгенівна; Посвятенко, Наталія Іванівна; Мельник, Тамара Василівна (НТУ "ХПІ", 2015)
Монографія присвячена дослідженню розвитку прикладних технічних наук в Україні в першій половині ХХ ст. Висвітлено внесок та уточнено історичні факти діяльності окремих фахівців, які працювали в Харківському технологічному та політехнічному інститутах. Розраховано на викладачів, студентів та всіх, хто цікавиться історією науки і техніки.

The monograph summarizes its authors’ scientific studies in the main areas of technology and technical education in Ukraine, since the turn of the XIX and XX centuries and ending at the 70s of the last century, and shows the general trends in the development of various sciences and forms of their organization based on example of the Kharkiv Polytechnic Institute. Approximately 90-years' period of development of applied engineering sciences in Ukraine on the basis of the experience of the Kharkiv Polytechnic Institute is analyzed in the monograph. The book provides an overview of science development, the origins of many specific features formation that determine its current position. The authors pay due attention to scientific and technical schools of M. F. Semko, V. M.Khrushchev, P. P. Kopniaev, V. I. Atroshchenko and other personalities – the leaders of those schools. The publication is designed for teachers, students and anyone interested in the history of science and technology.
Essays on history of applied technical sciences development in Ukraine. From the experience of Kharkiv Polytechnic Institute
Keywords: історія НТУ "ХПІ"; Харківський технологічний інститут; різання; машинобудування; електротехніка; технологія хімічна; Зворикін К. О.; Кнаббе В. С.; Тір В. Е.; Погорєлко О. К.; Пильчиков М. Д.; Клобуков М. П.; Копняєв П. П.; Гемеліан В. О.; Орлов Є. І.; Ададуров І. Є.